Features of the Metabolic Syndrome in the Berlin Fat Mouse as a Model for Human Obesity - Hantschel, Claudia (Obes Facts, 2011)
BACKGROUND: The Berlin Fat Mouse BFMI860 is a polygenic obesity mouse model which harbors a natural major gene defect resulting in early onset of obesity. To elucidate adult bodily responses in BFMI860 mice that develop juvenile obesity, we studied features of the metabolic syndrome at 20 weeks. METHODS: We examined fat deposition patterns, adipokines, lipid profiles in serum, glucose homeostasis, and insulin sensitivity in mice that were fed either a standard maintenance (SMD) or a high-fat diet (HFD). RESULTS: Like many obese humans, BFMI860 mice showed hyperleptinemia accompanied by hypoadiponectinemia already at SMD that was further unbalanced as a result of HFD. Furthermore, BFMI860 mice had high triglyceride concentrations. However, triglyceride clearance after an oral oil gavage was impaired on SMD but improved on HFD. The oral and intraperitoneal glucose as well as the insulin tolerance tests provided evidence for reduced insulin sensitivity under SMD and insulin resistance on HFD. BFMI860 mice can maintain normal glucose clearance over a wide range of feeding conditions according to an adaptation via increasing the insulin concentrations. CONCLUSIONS: BFMI860 mice show obesity, dyslipidemia, and insulin resistance as three major components of the metabolic syndrome. As these mice develop the described phenotype as a result of a major gene defect, they are a unique model for the investigation of genetic and pathophysiological mechanisms underlying the observed features of the metabolic syndrome and to search for potential strategies to revert the adverse effects under controlled conditions.